Effect of body condition score on reproductive performance of Chokla ewes - MAURYA, V P; KUMAR, S; KUMAR, D; GULYANI, R; JOSHI, A; NAQVI, S M K; ARORA, A L; SINGH, V K (The Indian Journal of Animal Sciences, 2011)
Body condition scoring (BCS) is a simple, non-invasive, time saving and beneficial technique to rank ewes according to their body reserve by sight and touch. The aim of the present study was to evaluate the impact of different BCS on reproductive performance of Chokla ewes in semi-arid region of India. Adult Chokla ewes (150) were used to study the effect of body condition score (BCS) on lambing rate and birth weight of lamb. Ewes were classified as per their BCS on 1 to 5 scale of half unit increment with 1 being an extremely thin and a 5 being fatty ewe. The ewes of 2.5, 3.0 and 3.5 BCS were marked as group1 (G1), group 2 (G2) and group 3 (G3), respectively. The heart girth (HG), pin shoulder length (PSL) and body weight of ewes were recorded at the time of mating. The gestation length, lambing rate and birth weight of lamb were also recorded during experiment. The HG, PSL and body weight of G1 ewes were significantly lower as compared to G2 and G3 groups ewes. The highest lambing rate was obtained in ewes of G2 group followed by ewes of G3 and G1 groups. The birth weight of lambs born from ewes of G1 group was significantly (P<0.05) lower as compared to ewes of G2 and G3 groups. The results indicated that the BCS of 3 or 3.5 at the time of mating resulted higher lambing rate and as well as more birth weight of lambs per lambing. Hence, attempt should be made to maintain majority of the ewes in the BCS of 3 to 3.5 during mating to get optimum productivity. Â